Respuesta :

Answer:

y=-3

x=1

(1,-3)

Step-by-step explanation:

5x+4y=-7

-5x-2y=1

Cancel +5x - 5

     2y=-6

      y=-3

5x-12=-7   or    -5x+6=1

5x=5                -5x=-5

x=1                     x=1

Answer:

y = -3, x = 1

or

(1, -3)

Step-by-step explanation:

5x + 4y = -7

-5x - 2y = 1

add the two equations together

0x + 2y = -6

2y = -6

2y/2 = -6/2

y = -6/2

y = -3

now substitute y = -3 into either of the equations

5x + 4y = -7

5x + 4(-3) = -7

5x - 12 = -7

5x = -7 + 12

5x = 5

x = 1

ACCESS MORE